(untitled) (Interdisciplinary Studies Journal, 2026)
This article examines Brazil’s international responsibility before the Inter-American Court of Human Rights from 2020 to 2025, focusing on recurring patterns of violations and on the State’s responses to international determinations. It assumes that the American Convention on Human Rights is binding within the Brazilian legal order, generating domestic normative effects through the duty to align State practices with conventional standards and the Court’s jurisprudence. The study adopts a qualitative, documentary approach grounded in judgments, institutional communications, and incorporation-related legal instruments, systematizing cases by year and by types of violations. The findings indicate persistent structural shortcomings in investigative due diligence, judicial protection, and prevention of violations affecting vulnerable groups, along with ongoing obstacles to full compliance with reparatory measures. The article concludes that the Court’s intervention functions as a corrective mechanism for institutional accountability deficits while simultaneously exposing enduring challenges to domestic implementation and State accountability.